Undocumented Uruguayan immigrants : biliteracy and educational experiences - Pessoa, Silvia, 1977- (New Americans (LFB Scholarly Publishing LLC), 2010)
Pessoa provides valuable insights into the educational experiences of undocumented immigrant adolescents in urban schools in the U.S. She calls attention to the impact of undocumented status on educational attainment as it prevents students from fully concentrating on their schooling and limits immigrant students? motivation to succeed academically and achieve higher education. However, despite the sociocultural and political constraints faced by undocumented immigrants, individual differences in the form of cultural capital, previous schooling experiences, literacy practices, and attitudes pr.